Penerapan Metode Pembelajaran Daring (Online) melalui Aplikasi Berbasis Android saat Pandemi Global - Agus Wilson (Universitas Indraprasta PGRI Jakarta, 2020)
This study is based on the global pandemic experienced throughout the world, especially Indonesia. The presence of the Covid-19 Virus pandemic has an impact on various fields, one of which is education. In Indonesian education, for 14 days, even more, the whole teaching and learning activities were suspended, and the implementation of the National Examination was also postponed. Changes in teaching methods must also be made online. Many social media applications that can be used, but not all of these applications have a feature and appropriate facilities and attractive to be used as teaching materials to the students. This study used quantitative and qualitative methods. 30 students were chosen randomly at one of the private universities in Jakarta. Collecting and analyzing data directly from respondents through the questionnaire is a quantitative method that the author used. While, qualitative methods used was library research techniques to support the results of collecting data through questionnaires on the use of applications based on Android. This study is expected to present a selection of the proper application to assist the learning process so that it has implications on improving the students' understanding and activities.